FAKTOR PERSEPSI INDIVIDU DALAM PENGEMBANGAN PERIKANAN LINTAS BATAS - Far Far, Romelus; Haluan, John; Baskoro, Mulyono S.; Nikijuluw, Victor (Jurnal Teknologi Perikanan dan Kelautan, 2017)
Manage of fisheries resource in border area would dependent about as long as behaviour and perception of community to response their problems. This paper would analyses about factor of individual perception to development fisheries transboundary such as fitting of historical, fishing gears, production, and marketing location; knowledge source about owner region and partial model of fishermen perception in Lirang, Wetar and Kisar Islands. Partial model of individual perception TCIF (Transboundary Commuters for Illegal Fishing) are e -1,372 + 0,846 SPKW + 1,029 PAN-TL or P (TCIF_ individual perception) = f (SPKW, PAN-TL)